Integrating publications in the social science doctoral thesis by publication - Mason, S.; Merga, Margaret (Routledge, 2018)
While still more common in the sciences, the Thesis by Publication (TBP) is gaining increasing popularity in the social sciences. However, we argue that norms and possibilities around accepted possible structures for this thesis form are still very much emergent, with a paucity of research concentrating on this area. As a consequence, doctoral students may lack adequate guidance about structural possibilities; there may be over-dependence on imitation of structural features of the traditional thesis, which could potentially compound issues of repetition; and greater clarity may be needed for the purposes of examination and composition of university policy. To respond to this gap in the research, we subjected 153 theses by publication in the social sciences produced between 2014 and 2017 in Australian universities to text-level structural analysis, in order to identify structures used in the contemporary TBP. Our research highlights 11 structural choices for the contemporary TBP observed in the data, also touching on possible motivations for and benefits of the varying approaches. We also highlight areas in need of further discussion and research that arise from the multiple structural possibilities emerging in the data.